2010
DOI: 10.1590/s1982-45132010000300011
|View full text |Cite
|
Sign up to set email alerts
|

A descentralização da política nacional de ATER: uma experiência nos assentamentos de reforma agrária no noroeste mineiro - Brasil

Abstract: RESUMO:A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
1
0
3
Order By: Relevance
“…Se trata, en definitiva, de la puesta en práctica de un modelo de extensión difusionista, orientado a promover una agricultura "moderna", pese a que en lo institucional se hable de un modelo participativo o territorial (Selis, 2012), alejado del difusionismo. En paralelo, otros autores son críticos frente a la implementación de un modelo de extensión productivista, es decir, tan focalizado en la dimensión productiva que no considera los factores sociales (Almeida, Oliveira & Xavier, 2010;Zuin et al, 2011). En este sentido, Rodríguez (2009) afirma que la supuesta "falta…”
Section: • 49unclassified
“…Se trata, en definitiva, de la puesta en práctica de un modelo de extensión difusionista, orientado a promover una agricultura "moderna", pese a que en lo institucional se hable de un modelo participativo o territorial (Selis, 2012), alejado del difusionismo. En paralelo, otros autores son críticos frente a la implementación de un modelo de extensión productivista, es decir, tan focalizado en la dimensión productiva que no considera los factores sociales (Almeida, Oliveira & Xavier, 2010;Zuin et al, 2011). En este sentido, Rodríguez (2009) afirma que la supuesta "falta…”
Section: • 49unclassified
“…Logo, Almeida et al (2010) relatam que a baixa ação das assistências técnica e extensão rural resultam em uma má transmissão das informações necessárias para a produção agrícola e pecuária, especialmente para aqueles produtores que residem e trabalham em áreas de reforma agrária, dificultando a disseminação do conhecimento a respeito da certificação orgânica de produtos, como apontam diversas pesquisas (Navas, 2019;Navas et al, 2021;Souza Júnior e Oliveira, 2021).…”
Section: Resultsunclassified
“…However, the results showed that more non-settled farmers than the settled ones know what farm certification means. According to Almeida et al (2010), the experience of land reform in Brazil and the technical assistance provided to this area is recent and marked by weak structure and service delivery. Therefore, the poor quality of the technical assistance and the consequent poor transmission of information to those who live in the settlements hinder the dissemination of knowledge on farm certification.…”
Section: Discussionmentioning
confidence: 99%